An actor survives. Issue 1 (2nd January 2018) - Kubikowski, Tomasz
Abstract: Stanislavski's last fully finished book: "The Actor's Work on Themselves, " better known in its English version as An Actor Prepares, can be regarded not as a mere handbook of acting. It is, even more, a meditation on survival and how to make theatre a tool for survival, by transferring on stage the fundamental processes of performance, used by the human being to cope with the world. Hence the double meaning of the Russian term пepeживaниe : "living through" or "surviving." In the numerous lectures and exercises contained within the book, and serving the above purpose, Stanislavski's seems to employ the mechanisms of human consciousness, which have been understood and described well at the end of the twentieth century by the neurophilosophers, especially Gerald Edelman.